Buffalo International Fair March - Louis H. Plogsted:::::::::
Piano score, 6 p. On cover: Dedicated to the Buffalo international fair. Also on cover are lithographs of the composer and a proposed fair building by Courier Lith. Co., Buffalo Sketch of proposed Art Building, Marling & Burdett Architects, on verso of last leaf.